Հայոց ցեղասպանության ականատես վերապրողների վկայությունները որպես պատմափաստագրական վավերագրեր - Վերժինե Սվազլյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Начиная с 1956 года, по собственной инициативе, в Армении и, частично, в Диаспоре были записаны устные народные воспоминания и песни исторического характера (армянские и туркоязычные), изложенные свидетелями-очевидцами из 70 местностей Западной Армении, Киликии и Анатолии. Эти материалы передали спасшиеся от Геноцида представители старшего поколения репатриантов. Since 1956, by our own initiative, we have inscribed oral memoirs and folk songs of historical character (in Armenian and Turkish languages) in Armenia and partly in the Diaspora, they have been narrated and sung by Armenian repatriates, representatives of the senior generation of eye-witnesses, miraculously saved from the Genocide and deported from 70 localities of Western Armenia, Cilicia and Anatolia.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)